English in the 4th grade in Iceland : exploring exposure and measuring vocabulary size of 4th grade students - Ásrún Jóhannsdóttir 1972- (2010)
The main aim of the pilot study presented in this article, was to develop and validate survey items and vocabulary tests intended to seek an answer to the question: What is the nature and size of the English vocabulary of 4th grade students in Iceland at the beginning of formal instruction? The study that is introduced in this article aims to examine the lexical proficiency of 4th grade students in Iceland at the onset of instruction, identify the factors that motivate students to learn English at this early age, and examine the amount and type of English young children are exposed to prior to beginning English studies in school. The results show that the items related to exposure to English demonstrated a high internal consistency reliability, Cronbach’s α = .82, proving reliability. Additionally, a correlation coefficient calculation demonstrates a consistency between a yes/no vocabulary size test and a Vocabulary Knowledge Scale test that validates the instruments. In addition, a significant positive relationship is established between test outcomes, on one hand, and factors such as listening to music and watching television in English on the other. Helstu markmið forkönnunnar sem greint er frá í þessari grein var að þróa og forprófa spurningakönnun og orðaforðapróf sem ætlað er að leita svara við eftirfarandi spurningu: Hvað er eðli og stærð á enskuorðaforða hjá nemendum í 4. bekk á Íslandi í byrjun formlegrar kennslu? Rannsóknin sem kynnt er í þessari grein miðar að því að kanna orðaforða og færni í 4. bekk á Íslandi í upphafi kennslu til að greina þá þætti sem hvetja nemendur til að læra ensku á þessum unga aldri. Einnig að kanna magn og tegund af ensku sem börn verða fyrir áhrifum frá áður en formlegt enskunáms hefst í skólanum. Niðurstöður sýna mikinn innri áreiðanleika spurninga sem skoða áhrif ensku, Cronbach’s α = .82, sem sannar áreiðanleika könnunarinnar. Útreikningar sýna einnig að samræmi fannst milli orðaforðaprófa sem styrkja gildi prófana auk þess sem jákvæð tengsl fundust milli útkomu prófa, ...